COMPARATIVE ANALYSIS OF PERSONAL DISPOSITION IN FREESTYLE AND GRECO-ROMAN WRESTLERS - I. Iliev (Trakia Journal of Sciences)
The purpose of the study was to reveal the characteristics of personal disposition by determining the goal orientation of wrestlers. The first study was conducted in 2023, and we compared these results with the results obtained from a study conducted in 2011. Sixty Freestyle and Greco-Roman wrestlers took part in the study. Methods: Task and Ego Orientation in Sport Questionnaire – TEOSQ was used. Variation analysis, descriptive statistics, and comparative analysis (the Mann-Whitney criteria) were applied. The mathematical and statistical processing packages IBM SPSS v 23.0 and Microsoft Office Excel 2016 were used. Results: The variation analysis of the experimental data showed that the subjects generally demonstrated a higher task orientation than ego orientation. The comparative analysis of the goal orientation between the groups showed that there was no statistically significant difference between them. As the orientation to the task prevailed over the ego orientation, this confirmed the hypothesis that in most of the studied persons, the goal orientation was aimed at the masterful performance of the tasks. Conclusion: The obtained data are of essential importance for increasing the effectiveness of sports training, as the conducted research expands the picture of sports activity with the manifestations of goal orientation and its reflection on the personality qualities of wrestling competitors.